Superparamagnetic Core–Shell Metal–Organic Framework Fe3O4/Cu3(btc)2 Microspheres and Their Catalytic Activity in the Aerobic Oxidation of Alcohols and Olefins. Issue 30 (19th September 2016) - Li, Jie; Gao, Hongyi; Tan, Li; Luan, Yi; Yang, Mu
Abstract : Core–shell structured Fe3 O4 /Cu3 (btc)2 (btc = 1, 3, 5‐benzenetricarboxylate) microspheres have been successfully synthesized by coating the metal–organic frameworks on poly(acrylic acid) (PAA) functionalized Fe3 O4 microspheres by the layer‐by‐layer assembly method. The MOF composite exhibited excellent catalytic activity in the aerobic oxidation of alcohols and the epoxidation of olefins due to the porosity of MOFs and large amount of readily accessible Cu 2+ . Furthermore, the catalyst could be easily segregated from the catalytic system by using an external magnetic field due to its magnetic properties. The heterogeneous catalyst displayed good reusability and broad reagent scope in the aerobic oxidation of alcohols and epoxidation of olefins. Abstract : Core–shell metal–organic framework Fe3 O4 /Cu3 (btc)2 microspheres have been successfully synthesized by a one‐step solvothermal method and a subsequent layer‐by‐layer strategy. The superparamagnetic heterogeneous catalyst exhibits efficient activity and high selectivity in the aerobic oxidation of alcohols and the epoxidation of olefins. The catalyst shows excellent recyclability.